Development of a core patient-centred outcome set for adults living with obesity: a modified delphi-based international consensusResearch in context - Teferi Mekonnen; Leanne Staniford; Spencer Connell; Zofia Das-Gupta; Umanga DeSilva; Yasmine Saoud; Isabel Miller; Mohapradeep Mohan; Simon Nienhuijs; Megha Poddar; Vaishali Chetan Deshmukh; Marli Conradie-Smit; et al. (EClinicalMedicine)
Summary: Background: Obesity is a chronic disease linked to over 200 health conditions, reduced quality of life, and increased mortality. Despite the availability of multimodal treatments, there is a lack of standardised, patient-centred outcome measures to effectively assess and improve clinical care. This project aimed to define a core set of standardised outcome measures for adults with obesity, incorporating both patient-reported and clinician-reported outcomes. Additional objectives included determining the optimal measurement frequency and identifying case-mix variables essential for risk adjustment. Methods: The International Consortium for Health Outcomes Measurement (ICHOM) established the Obesity Working Group (OWG), composed of 29 international experts and individuals living with obesity. Members were selected based on their expertise in obesity care and research and represented 21 countries. The development process, conducted from May 2023 to July 2024, began with a kick-off meeting to define scope, followed by eight virtual meetings. A comprehensive literature review informed the identification of relevant clinical outcomes, patient-reported outcomes, treatment-related complications, and case-mix variables. A three-round Delphi process was used to reach consensus on key outcomes and follow-up intervals. Outcomes were included in the final set if at least 80% of OWG members rated them between 7 and 9 on a 9-point scale. Validation was conducted through surveys with 95 patients and 106 healthcare professionals from fields such as dietetics, obesity medicine, and general practice. Findings: The OWG developed a standardised set of 20 outcome measures, comprising 17 core measures and 3 population-specific measures. These span domains including physical health, psychosocial well-being, health behaviours, body functioning, and adverse events. Specific measures were also developed for bariatric surgery and female reproductive health (both pregnant and non-pregnant individuals). Key case-mix factors and appropriate follow-up periods were defined to support global consistency in reporting. Interpretation: Adoption of this standardised outcome set enables clinicians, patients, and stakeholders to identify care gaps, monitor outcomes, and evaluate the quality of obesity care against global benchmarks. Implementation can support the creation of a robust international data resource to guide research, inform clinical practice, and shape policy and guidelines for adult obesity treatment. Limitations include limited geographical diversity in validation surveys, the exclusion of internalised weight bias due to a lack of validated measurement tools, and limited applicability to individuals with obesity and multiple comorbidities. Funding: Novo Nordisk, Eli Lilly, and Boehringer Ingelheim International GmbH.